Looking the part (to me): effects of racial prototypicality on race perception vary by prejudice - Cassidy, Brittany S. (Soc Cogn Affect Neurosci, 2017)
Less racially prototypic faces elicit more category competition during race categorization. Top-down factors (e.g. stereotypes), however, affect categorizations, suggesting racial prototypicality may enhance category competition in certain perceivers. Here, we examined how prejudice affects race category competition and stabilization when perceiving faces varying in racial prototypicality. Prototypically low vs high Black relative to White faces elicited more category competition and slower response latencies during categorization (Experiment 1), suggesting a pronounced racial prototypicality effect on minority race categorization. However, prejudice predicted the extent of category competition between prototypically low vs high Black faces. Suggesting more response conflict toward less prototypic Black vs White faces, anterior cingulate cortex activity increased toward Black vs White faces as they decreased in racial prototypicality, with prejudice positively predicting this difference (Experiment 2). These findings extend the literature on racial prototypicality and categorization by showing that relative prejudice tempers the extent of category competition and response conflict engaged when initially perceiving faces.